2018
DOI: 10.1002/pa.1830
|View full text |Cite
|
Sign up to set email alerts
|

Does leadership lessen turnover? The moderated mediation effect of leader–member exchange and perspective taking on public servants

Abstract: Drawing on motivated information processing theory and social exchange theory, this research investigates the mediating effects of leader-member exchange and moderating impact of perspective taking in the relationship among transformational leadership and turnover intentions of public servants. Using a sample of 385 respondents from different public sectors across Pakistan, we found a negative association of transformational leadership with the turnover intentions, which is further mediated by leader-member ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 110 publications
3
9
0
Order By: Relevance
“…In addition, when these employees have good inclusive leaders having alike intrinsic motivation, the chances of creative performance become maximum. These findings are in line with the concept of social exchange theory (Blau, 1964;Siyal, 2018;Siyal & Peng, 2018), whose main tenet is that if the employees get favor and support from their leaders, they develop a feeling of paying back (reciprocation), which in turn, proves useful in building a good relationship between leaders and employees. Moreover, when the inclusive leaders facilitate employees with socioemotional support, the employees feel obligated to repay their leaders.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, when these employees have good inclusive leaders having alike intrinsic motivation, the chances of creative performance become maximum. These findings are in line with the concept of social exchange theory (Blau, 1964;Siyal, 2018;Siyal & Peng, 2018), whose main tenet is that if the employees get favor and support from their leaders, they develop a feeling of paying back (reciprocation), which in turn, proves useful in building a good relationship between leaders and employees. Moreover, when the inclusive leaders facilitate employees with socioemotional support, the employees feel obligated to repay their leaders.…”
Section: Discussionsupporting
confidence: 82%
“…After the employees switch the organizations, they let the organizations bear the expenditure of hiring and training of the new employees. Researchers discuss the quit intention is easy to evaluate and foresee as compared with actual turnover (Firth et al, 2004;Nadiri & Tanova, 2010) and others predict to be very good indicators of the management practice and leadership (Guchait & Cho, 2010;Siyal, 2018;Siyal & Peng, 2018). Moreover, prior studies related to private and business sectors have found the moderate relationship among the intentions to quit and the turnover behavior (Macky & Boxall, 2007), while the recent studies found that the same relationship is stronger in the context of the public sector organizations (Carmeli & Weisberg, 2006; Y. J.…”
Section: Intention To Quitmentioning
confidence: 99%
“…In recent years, leader-member exchange (LMX) has gained a lot of attention from researchers because of its consequences on employees' work performance (Epitropaki et al, 2016;Schwepker, 2017;Siyal and Peng, 2018). LMX is one of the most prominent theories that deal with the dual relationship between a leader and the subordinates (Graen and Wakabayashi, 1994;Brower et al, 2000;Pellegrini et al, 2010).…”
Section: Introductionmentioning
confidence: 99%